PENGARUH UKURAN PERUSAHAAN, MANAJEMEN LABA DAN GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Yusmaniarti Yusmaniarti; Marini Marini; Ahmad Junaidi; Elsa Febiola (Universitas Muhammadiyah Jember, 2022)
This study aims to determine the effect of Company Size, Earnings Management and Good Corporate Governance as proxied by the size of the board of commissioners, institutional ownership and managerial ownership. Towards Firm Value (Empirical Study on Manufacturing Companies in the Food and Beverage Sub-Sector Listed on the Indonesia Stock Exchange). This study is a quantitative study with a population of manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX). The sampling technique used the purposive sampling method and 39 samples were obtained from 13 manufacturing companies in the food and beverage sub-sector in the 2018-2020 observation period. The type of data is secondary data sourced from annual reports and financial reports of manufacturing companies in the food and beverage sub-sector. The study was conducted with a quantitative approach using data analysis techniques, namely multiple linear regression analysis and partial significant test (T test). The results showed that firm size (X1) 0.393 0.05 had no effect on firm value, earnings management (X2) 0.544 0.05 had no effect on firm value, proxy for board of commissioners size (X3) 0.5720.05 had no effect on firm value, proxy for institutional ownership (X4) 0.393 0.05 had no effect on firm value, and proxied managerial ownership ( X5) 0.942 0.05 has no effect on firm value.